The Model of Agrobusiness Partnership of Trigona Honey Bee Which Was Developed by The Community Around the Forest Area in Amonggedo District, Konawe Regency, Southeast Sulawesi Province - Indonesia - La panga,; Wayan Puguh,; Erni Dangi,; Hastian, (International Journal of Management and Education in Human Development, 2022)
This study aims to develop an Agribusiness partnership model for Trigona Honey bee, for the community around the Forest Area in Amonggedo District, Konawe Regency, Southeast Sulawesi Province. The Research method used was descriptive qualitative analysis. The results of this study obtained pieces of information: (1) Identification of the biological attributes and habitual of the Trigona honey bee, as well as the perception of the community around the forest area towards the Trigona honeybee, (2) the TheDesigning of the Agribusiness Partnership model, based Constrain factors those are: a). Production management of Trigona Honey Bee cultivation, b) Management of facilities and infrastructure for the production of Trigona honey bees and their institutions, c) The application of technology for Harvest processing of the Trigona honey bee, Sp, d) Marketing distribution channels and other trading partners. (3) Developing the Model Agribusiness partnership of Trigona honey bee which was developed by the community around the forest area in Amonggedo District, Konawe Regency. (4) The analysis and validation of the success level of the Agribusiness partnership model for the community around the forest area are at an average of 87.5% or a very good category evaluation model. 5. The validation of the Agrobussines partnership model with a very good category, are shown the prospectively and sustainability for develop in the community around the forest area in Amonggedo District and Konawe Regency Sout east Sulawesi Province.